The Relationship of Parent-Child Interaction in Developing Effective Communication in Early Childhood - Desmita, Desmita; Rahmadani, Suci; Kharisma Diyenti, Adella; Warmansyah, Jhoni; Silvianetri, Silvianetri; Binti Fakaruddin, Noor Annis Azwin (Universitas Islam negeri Mahmud Yunus Batusangkar, 2023)
The family is the first and main educational environment for children because that is where children start with everything until they suffer and understand that all of this cannot be separated from the family's responsibilities. So the aim of this research is to build good relationships, positive and open interaction between parents and children can help build good relationships. This research uses a correlation type quantitative research method that connects the relationship between parents and children in developing effective communication in early childhood at IT Puti Tareno Bayan Kindergarten. The results of this research show that there is a relationship between parent and child interactions in developing effective communication in early childhood. The results of this research show that there is a relationship between parent and child interactions in developing effective communication in early childhood.┬á┬á